Exchange rate regimes and trade - Adam, C; Cobham, D (Wiley, 2007)
A 'new version' of the gravity model is used to estimate the effect of a full range of de facto exchange rate regimes on bilateral trade. The results indicate that, while participation in a common currency union is typically strongly 'pro-trade', other exchange rate regimes which lower the exchange rate uncertainty and transactions costs associated with international trade are significantly more pro-trade than the default regime of a "double float". They suggest that the direct and indirect trade-creating effects of these regimes on uncertainty and transactions costs tend to outweigh the trade-diverting substitution effects. Tariff-equivalent monetary barriers associated with each exchange rate regime are also calculated.